بناء نظام إنترنت الأشياء معتمد على السحابة باستخدام بروتوكول CoAP - دنده رضوان; غدير رشا (Latakia University Journal -Engineering Sciences Series, 2019)
Internet of Things (IoT) and cloud computing are two very different technologies, Their massive adoption and usage is expected to increase further, making them important components of the future internet. Internet of Things consists of a set of things that are connected with each other using the internet in order to provide smart services to the end users. Generally, all of these things lack storage capacities and have limited processing power. Cloud computing on the other hand is a technology that has unlimited storage and processing capabilities, hence most of the problems plaguing the IoT can be solved, even partially, in the cloud. In this paper we present a complete structure of an IoT system that can detect faces, recognize them, and predict age based on smart algorithms provided by the cloud using Constrained Application Protocol (CoAP) to communicate between nodes and cloud. This protocol is intended for real-time systems made up of small, low-cost IoT devices with limited resources. The performance of the server was tested by the CoAPBench tool.The results show that CoAP protocol reduces the burden on the IoT devices and improves the performance of cloud productivity by serving a large number of applications from connected devices. بناء نظام إنترنت الأشياء معتمد على السحابة باستخدام بروتوكول CoAP إنترنت الأشياء (IoT) والحوسبة السحابية, تقنيتان مختلفتان تماماً, ولكنهما تعتبران جزءاً أساسياً من مستقبل الإنترنت. إنترنت الأشياء يعتمد على مجموعة من الأشياء تتصل مع بعضها البعض باستخدام الإنترنت لتقديم خدمات ذكية, ولكن كل هذه الأشياء تعاني من مشاكل التخزين وقدرات المعالجة المحدودة. من ناحية أخرى فإن الحوسبة السحابية تقنية أنضج بكثير من إنترنت الأشياء من حيث امتلاكها طاقات غير محدودة فيما يتعلق بالتخزين و قدرات المعالجة, و بالتالي فإن معظم المشاكل التي تعاني منها إنترنت الأشياء من الممكن حلها ولو بشكل جزئي في السحابة. في هذا البحث نقدم بنية كاملة لنظام إنترنت الأشياء لتحديد وتمييز الوجوه , وتوقع العمر بالاعتماد على الخوارزميات الذكية المقدمة من قبل السحابة. وباستخدام بروتوكول التطبيقات المقيدة (CoAP) للتواصل ما بين العقد والسحابة. هذا البروتوكول مخصص لأنظمة الزمن الحقيقي المتكونة من أجهزة IoT صغيرة الحجم ذات تكلفة قليلة و محدودة الموارد. تم اختبار انتاجية المخدم المنجز عن طريق الأداة CoAPBench حيث أظهرت النتائج أن بروتوكول CoAP يخفف العبء على عقد IOT كما أنه يحسن من أداء إنتاجية السحابة بتخديمها عدد كبير من الطلبات من الأجهزة المتصلة.